Lotus 1-2-3 Release 2.2 : Setting Up 1-2-3 and Reference Manual. (Cambridge, Massachusetts : Lotus Development Corp., 1989)
Setting Up 1-2-3 describes the procedures for installing Lotus 1-2-3 and the Allways spreadsheets publishing add-in. Many of these procedures must be completed before your can use either programs. Setting Up 1-2-3 also explains how to start 1-2-3 and provides specific information about using Release 2.2 with different computers.